2018
DOI: 10.1002/ange.201804368
|View full text |Cite
|
Sign up to set email alerts
|

Erneuerbare Polyether über die GaBr3‐katalysierte Reduktion von Polyestern

Abstract: Ein neues Konzept zur Synthese mittel‐ bis langkettiger aliphatischer Polyether beruht auf der GaBr3‐katalysierten Reduktion verschiedener Polyester mit TMDS als Reduktionsmittel. Eine Reihe linearer und verzweigter Polyester wurde synthetisiert und systematisch im Hinblick auf diese Reduktionsstrategie untersucht, wodurch die Eignung und Vielseitigkeit dieses Reduktionsverfahrens demonstriert werden konnten. Die mittel‐ und langkettigen Polyether wurden aus den entsprechenden Polyestern ohne oder mit geringfü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…8 Very recently, more sustainable step-growth polymerization approaches of polyethers have been reported. [9][10][11][12] For instance, Meier et al prepared polyethers by the catalytic reduction of polyesters. 12 Our group recently found that medium-to-long chain aliphatic homopolyethers could be easily prepared by the bulk self-condensation of alcohols in the presence of Non-Eutectic Mixture Organocatalyst (NEMO) based on methanesulfonic acid (MSA) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) (3:1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Very recently, more sustainable step-growth polymerization approaches of polyethers have been reported. [9][10][11][12] For instance, Meier et al prepared polyethers by the catalytic reduction of polyesters. 12 Our group recently found that medium-to-long chain aliphatic homopolyethers could be easily prepared by the bulk self-condensation of alcohols in the presence of Non-Eutectic Mixture Organocatalyst (NEMO) based on methanesulfonic acid (MSA) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) (3:1).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] For instance, Meier et al prepared polyethers by the catalytic reduction of polyesters. 12 Our group recently found that medium-to-long chain aliphatic homopolyethers could be easily prepared by the bulk self-condensation of alcohols in the presence of Non-Eutectic Mixture Organocatalyst (NEMO) based on methanesulfonic acid (MSA) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) (3:1). 13 As a result, highly semicrystalline polyoxyalkylenes with a number of As far as we know, there are no general rules that can unambiguously predict if a copolymer will display isomorphic, isodimorphic or no co-crystallization 14 .…”
Section: Introductionmentioning
confidence: 99%